Inhibitory effect of some medicinal plant extracts on some pathogenic fungi - Omer, Marwa; Raof, Ayyad; Hashim, Abdul-Karim (Iraqi Journal of Science, 2023)
Plants and their extracts preparations have been used as medicines against infectious diseases. In present work, Cassia senna (leaves), Piper nigrum (fruits) were extracted with different organic solvents to investigate their antifungal activities in vitro. However, the effective of plant extracts against some pathologic fungi (Tricophyton rubrum, T. tonsurans, T. violaceum, Microsporum audouinii, M. canis and M. gypseum) were evaluated at concentrations ranged between (0.005–5%) using agar diffusion methods and compared with standard antifungal drug (Clotrimazole). Results showed that methanol extract of C. senna and ethanol extract of P. nigrum displayed excellent inhibition on dermatophytes compared with standard antifungal drug, the MFC value for C. senna extract against dermatophyte isolates was (0.5%) except T. rubrum and M. canis (0.1%), the MIC was (0.05%). MFC value for P. nigrum extract against T. violaceum, M. audouinii and M. gypseum was (0.1%) while for M. canis was (0.05%), T. rubrum and T. tonsurans was (0.01%) and the MIC value was (0.005%). But MFC value for clotrimazole was (0.5%) and the MIC value was (0.1%). The yield of active compounds in C. senna and P. nigrum were (3, 6.7%) respectively. Also, the chemical compositions of these extracts were analyzed by FLC (Fast Liquid Chromatography) the result shows that the main components in C. senna were phenols, alkaloids and glycosides, while in P. nigrum were phenols, alkaloids and there was no terpens.